Energy Safety: Politics and Diplomacy - Anokhin, Michael; Grishin, Oleg (Przegląd Strategiczny, 2013)
There is a spectrum of approaches to understanding of the energy safety, policy, and diplomacy. Each country draws on the conditions of its power security. Global, regional and local levels of energy safety are identified. Nowadays, this problem is multidirectional and multidimensional. Aunique competitive advantage of Russia in the field of energy industry is used for solving its foreign policy issues. This tool will be applied in those cases and in that volume in which it will be necessary for maintenance of national interests. Energy resources and the transit infrastructure of Russia should be used effectively for strengthening of the role and the status of the Russian Federation on the global level.